Impact of Teledermatology on Skin Cancer Patients During COVID-19 - Yanara García Leyva; Kenia González González; Leyanis Elena de la Rosa Pérez; Dayana Céspedes García; Keimys Leyva Hernández (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: during the COVID-19 pandemic, there was difficulty in accessing dermatology consultations, making it impossible to prioritize skin cancer cases. A teledermatology system was designed and implemented, through mobile telephony, for the study of patients with this pathology. Objective: to evaluate the impact of the teledermatology system for the study of skin cancer in patients treated at the Guillermo Fernández Hernández-Baquero Dermatological Hospital during the COVID-19 pandemic. Methods: a descriptive study was carried out to evaluate the impact of teledermatology in 88 patients with lesions suspected of skin cancers, referred from Primary Care and treated at the Guillermo Fernández Hernández-Baquero Dermatological Hospital in the period since April 1 2020 until April 1, 2021. A teledermatology system was designed, of the teleconsultation type with the possibility of remote diagnosis, based on the exchange of images and texts, on an Android mobile device. The descriptive statistical method was used. The results were expressed in tables for better understanding. Results: basal cell carcinoma predominated in 63.6 %. The clinic pathological correlation for basal cell carcinoma was 96.4 %, by teledermatology and by face-to-face consultation, respectively. Simple agreement was 93.2 %. Disagreements were slight for 6.8 %. The level of satisfaction was 95.5 %, very satisfied with the applied teledermatology system. Conclusions: the teledermatology system has technical feasibility, is efficient, useful, with diagnostic accuracy, reliability and reproducibility, being effective in the diagnosis of skin cancer, in unfavorable epidemiological conditions such as the COVID-19 pandemic.